Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s11661-012-1547-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Solute Drag Effect on Ferrite Growth in Fe-C-X Alloys Using Controlled Decarburization Experiments

Abstract: International audienceThe kinetics of ferrite growth in the Fe-C-Co and Fe-C-Si systems has been quantified using controlled decarburization experiments. The Fe-C-Co system is a particularly interesting system since a large range of Co contents can be considered providing a suitable data set for examination of the composition dependence of the solute drag effect. Six Fe-C-Co alloys containing Co from 0.5 to 20 pct have been considered. Three Fe-C-Si alloys have also been considered and each has been transforme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 22 publications
0
19
0
2
Order By: Relevance
“…This is in contrast to previous studies of Fe-X-C systems, in which the substitutional solute X was varied. [1,17] Most importantly, the study of denitriding kinetics permits extension of the study to much lower temperatures than is possible using decarburization of Fe-Mn-C alloys. This is important for the study of kinetic transitions in ferrite growth mode which are currently the focus of much research in this field.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to previous studies of Fe-X-C systems, in which the substitutional solute X was varied. [1,17] Most importantly, the study of denitriding kinetics permits extension of the study to much lower temperatures than is possible using decarburization of Fe-Mn-C alloys. This is important for the study of kinetic transitions in ferrite growth mode which are currently the focus of much research in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Lee [29] studied the thermodynamics equilibrium of the Cr-Mn and the Fe-Cr-Mn systems, and the free energy parameters of the Fe-Cr binary alloy system were given. Qiu [30] found that the free energy of fcc structure and hcp structure in the Cr-Mn system was equal, i.e., the free energy difference was 0 when martensitic transformation occurred. Ohnuma et al [27] listed the thermodynamics parameters used in the calculation of the Fe-Co binary system and optimized the magnetic www.advancedsciencenews.com www.aem-journal.com parameters when they studied the phase equilibrium of the Fe-Co binary system.…”
Section: Thermodynamics Analysismentioning
confidence: 99%
“…As a first step of this validation, systematic laboratory experiments were conducted using Fe model alloys where ferrite growth was monitored using the method of controlled decarburization. 34,35 These experiments consist of reheating the specimen into the austenite single-phase region in an atmosphere of wet hydrogen. The oxygen potential of this atmosphere is high enough to remove carbon from the specimen but too low to oxidize iron.…”
Section: Ferrite Growth In Fe Model Alloysmentioning
confidence: 99%
“…The simplicity of the growth geometry along with the availability of accurate thermodynamic and kinetic databases allows one to use these experiments to deduce the contact conditions at the migrating ferrite-austenite interface and to determine the magnitude of solute drag in Fe-C-X model alloys (X: Ni, Mn, Si, Mo, etc.). 35 A self-consistent model has been developed to describe the observed ferrite growth. 36 The model captures the time evolution of interfacial contact conditions for substitutional and interstitial solutes.…”
Section: Ferrite Growth In Fe Model Alloysmentioning
confidence: 99%